Tanggungjawab Penyedia Jasa Konstruksi Terkait Kegagalan Konstruksi dalam Pengadaan Barang/Jasa Pemerintah - Fitri Yanni Dewi Siregar; Sunarmi Sunarmi; Mahmul Siregar; Detania Sukarja (USU LAW JOURNAL, 2019)
Abstract. A development project is a legal act carried out by a person or business entity on the basis of an agreement or contract at a certain time and place, which is needed by a user of goods or services in this case the government. In the implementation of construction work, there are certainly many factors that can trigger the failure of construction work, one of them is the incompability of construction work contract, work plan and terms, and the conditions in the field. This mismatch becomes a construction failure that will have an impact on the vulnerability of the building so that there is a risk of failure in the building which can even cause casualties. The failure of construction provisions regarding the rights and obligations of users and service providers in Government Procurement of Goods / Services which has been regulated and stipulated in the construction work contract provisions in the procurement of government goods/services and legislation related to construction services. Forms of legal liability if in the implementation of construction work things happen that are not in accordance with the agreement of the parties, the service users give the service provide an opportunity for service providers to repair and make these improvements will be stated in the contract addendum. To protect the parties, especially those who are disadvantaged in carrying out construction work, the form of legal protection that can be done is by providing preventive legal protection is related to the type of coverage that can be agreed on in construction work contracts that include guarantees and repressively if the implementation of one or both parties commit negligence which can intentionally caused casualties.   Keywords: procurement, construction failure, construction contract